Cellular Endocytosis and Gene Delivery - Jennifer Ziello; Yan Huang; Ion S. Jovin (2010)
Endocytosis is the process by which cells take up macromolecules from the surrounding medium. The best-characterized process is the so-called clathrin-dependent endocytosis, although much is also currently known about clathrin-independent endocytic processes such as those involving caveolae and lipid rafts. An understanding of endocytosis and the cellular trafficking that occurs thereafter has a great deal of relevance to current molecular medicine. Gene therapy, which is presently being investigated for its therapeutic potential in treating immunodeficiency and metabolic diseases, cancer and heart disease, employs a variety of viral and nonviral vectors, which can be delivered to the target cells of the body and are subsequently endocytosed and dissembled. A variety of vectors can be used to deliver genes to organs invivo or cells exvivo. Various routes of vector delivery have been investigated. The mechanisms by which vectors such as adenoviruses, adeno-associated viruses, retroviruses and liposomes enter the cell are increasingly being investigated as the effort to increase the efficiency of gene therapy continues. This review focuses on mechanisms of endocytosis and how they relate to the internal trafficking of viral and nonviral vectors in gene therapy.